Rasch Model Analysis of Santri Reverence Morals Scale - Mufrihah, Arina; Supriatna, Mamat; Ahman, Ahman; Yudha, Eka Sakti; Nurihsan, Juntika (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2025)
Reverence, also known as ta’dzim in Pondok Pesantren (Islamic boarding schools), is a moral aspect which is taught to santri (students in Islamic boarding schools) as the most important value. Ta’dzim is delivered as an ethic, develops as a value, and grows to be part of a santri’s personality and standard behavior. This study aims to develop a valid and reliable Santri Reverence Morals Scale (SRMS) through the Rasch Model analysis. The scale was supervised under an expert judgement evaluation which was involved 7 experts and distributed to 95 participants (male santri aged between 13-23 years) who were selected through stratified random sampling. The Rasch Model analyzed output and the interpretation included data about instrument, items, and person. This study indicated that the Santri Reverence Morals Scale is very reliable, predominantly fits items, and is unidimensionally proven. In this paper, such shortcomings as hard items, misfit items, and bias items are also discussed and evaluated. The composite analysis of instrument, items, and abilities concluded that the SRMS is a questionnaire with high reliability and validity (the item separation value is 3.40 and Cronbach alpha score is 0.82). This initial instrument testing stage requires further development so that a high-quality questionnaire can be produced to measure and study the ta’dzim of santri.